5 Fermentation and extraction conditions optimization for the production of polysaccharides of Lepista sordida. (19th December 2016) - Meng, Fanxin; Wang, Lanying; Tang, Meng; Huang, Xiaomin; Wang, Di; Chen, Peizhou; Lei, Xi; Teng, Lirong
Abstract : Objectives: Lepista sordida (Schum.: Fr.) Sing . is a type of edible Agaricus mushroom. It exhibits several activities including immunomodulation, and antioxidant and anti-fungal properties. The objective of this investigation was to investigate the fermentation and extraction conditions of polysaccharides from the mycelium of L. sordida . Methods: This single parameter experiment was performed to identify the optimal culture conditions including culture temperature, culture cycle and initial pH. Furthermore, an orthogonal experimental design L9 (3 4 ) was used to evaluate the combination effects of carbon sources, nitrogen and minerals on the extracts from mycelia. Extraction conditions optimization including the ratio of water to material (v/w), temperature and extraction time based on response surface methodology was employed to identify the optimum conditions. Results: The maximum mycelium dry weight was obtained when cultured in an optimal composition of sucrose 30 g/L, yeast extract 6 g/L, KH2 PO4 0.1 g/L and MgSO4 1 g/L at temperature 28° C, culture cycles of 7 days and initial pH 7.0. The optimum conditions for polysaccharide extraction from L. sordida mycelia were a ratio of water to material of 72.1:1, temperature 92.6° C and time 2.9 hours. Under these conditions, the predictive and practical extraction efficiency was 16.5% and 16.5±0.1%, respectively. Conclusions: The results are helpful for building an efficient and controllable model to improve the extraction efficiency for industrial production of bioactive polysaccharides from L. sordida. Acknowledgments: This study as supported by the Guangdong Provincial College Students Innovation and Entrepreneurship Training Program (Nos. DC2016062 and DC2016063).